1994
DOI: 10.1007/bf00028864
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of P-type H+-ATPase genes from potato

Abstract: H(+)-ATPase cDNAs were identified in a potato leaf library using an Arabidopsis gene as a probe. Based on their sequences, the clones could be grouped into at least two classes. A similar classification was obtained from the analysis of sequence data from four tobacco genes. Both potato genes are expressed in all tissues analysed, higher levels of expression were found in leaves and stem than in roots and tubers. For both genes, no significant differences in level of expression could be detected under a variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…The increase in sucrose transport activity caused by modification of a conserved histidine in the first external loop (Lu and Bush, 1998) indicates that sucrose transporters may be directly regulated at the protein level. In addition, the amounts of mRNA for sucrose transporter SUT1 from potato are developmentally controlled and hormonally regulated (Riesmeier et al, 1993;Harms et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in sucrose transport activity caused by modification of a conserved histidine in the first external loop (Lu and Bush, 1998) indicates that sucrose transporters may be directly regulated at the protein level. In addition, the amounts of mRNA for sucrose transporter SUT1 from potato are developmentally controlled and hormonally regulated (Riesmeier et al, 1993;Harms et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in sucrose transport activity caused by modification of a conserved histidine in the first external loop (Lu and Bush, 1998) indicates that sucrose transporters may be directly regulated at the protein level. In addition, the amounts of mRNA for sucrose transporter SUT1 from potato are developmentally controlled and hormonally regulated (Riesmeier et al, 1993;Harms et al, 1994).Clearly, multiple kinetic components of sucrose uptake are present in leaves (Delrot and Bonnemain, 1981;Maynard and Lucas, 1982). As demonstrated by autoradiography, 14 C-sucrose, externally applied to source leaves of Vicia faba or Beta vulgaris , is taken up by mesophyll cells and phloem (Fondy and Geiger, 1977;Giaquinta, 1977;Delrot, 1981).…”
mentioning
confidence: 99%
“…It has been shown that various genes are expressed in the same organ. Moreover, even within the same cell type at the same developmental stage, at least two H + -ATPase genes are expressed (Harms et al, 1994;Hentzen et al, 1996;Moriau et al, 1999). In N. plumbaginifolia two different plasma membrane H + -ATPase genes, PMA2 and PMA4, are expressed in guard cells (Moriau et al, 1999).…”
mentioning
confidence: 99%
“…With such a phenomenon the amount of H + -ATPase might be increased under conditions requiring greater transport activity. The external signals result in changes in plant plasma membrane H + -ATPase gene expression, include salt (Niu et al, 1993;Binzel, 1995;JanickaRussak & Kłobus, 2007), low temperature (Ahn et al, 1999(Ahn et al, , 2000, heavy metals (JanickaRussak et al, 2008), dehydration (Surowy et al, 1991), light conditions (Harms et al, 1994), mechanical stress (Oufattole et al, 2000) and externally applied hormones (Frías et al, 1996).…”
mentioning
confidence: 99%
“…Multiple genes encoding PM H+-ATPases have been cloned in tomato (Lycopersicon esculentum; Ewing et al, 1990;Ewing and Bennett, 1994), Nicotiana plumbaginifolia (Boutry et al, 1989;Perez et al, 1992;Moriau et al, 1993), Arabidopsis fhaliana (Harper et al, , 1990(Harper et al, , 1994Pardo and Serrano, 1989;Houlne and Boutry, 1994), potato (Harms et al, 1994), rice (Wada et al, 1992;Ookura et al, 1994), and Vicia faba (L.E. Wimmers, unpublished data).…”
mentioning
confidence: 99%